Assessing Next Generation EU - Lorenzo Codogno; Paul van den Noord (London School of Economics and Political Science (LSE), European Institute, 2021)
The unprecedented fiscal package adopted by the European Council in the summer of 2020 1em1ptdubbed Next Generation EU1em1ptis vital for the recovery of the euro area from the pandemic shock. However, there are risks that targets will not be met and that it may prove difficult to muster the same degree of European 'solidarity' in the future. Computations with a stylised macroeconomic model indicate that an alternative approach, with ex ante risk sharing through the creation of a Eurobond and permanent fiscal capacity at the centre, would be at least as powerful, yet it would be more sustainable, automatic and timely.
Keywords: 330; Fiscal Policy; Business fluctuations; Safe sovereign assests; Fiscal capacity